Animal house - Turka, Laurence A. (The Journal of Clinical Investigation, 2008)
While the JCI was originally conceived as a journal that would integrate various scientific approaches to the examination of human physiology and pathophysiology, we now find many of its pages filled with animal models of human disease. Is this a good thing?